Kemas Ulang Informasi di Perpustakaan Universitas Respati Yogyakarta - Jayanti, Lida Dara; Masruri, Anis (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This paper uses a qualitative method with a descriptive approach. The aim of this writing is to narrate the repackaging of information in the form of scientific writing so that the overall aim of the essay is to support scientific search, learning and research. Repackaging information in the Yogyakarta Respati University Library is important in providing fast and efficient access. With the display provided, users are directed to log in with the previously registered username and password, and after that, they can enter keywords to explore the diverse collection of essays. Librarians have also posted the website address on the library desk to make it easier for users to access information. Although the Essay has several limitations, such as limited coverage and restrictions in subject matter, this resource still plays an important role in supporting research and scientific development in the university environment. Overall, repackage this information into a tool that advances scientific pursuits and makes it easier for users to pursue necessary knowledge.